Proline and ascorbic acid content in leaves of NERICA mutant rice lines and their parents under rainfed condition - Nuruzzaman, Md; Hassan, Lutful; Begum, Shamsun Nahar; Huda, Md Monjurul (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Proline and ascorbic acid are important osmolytes responsible for drought tolerance in rice. The present study was conducted to determine proline and ascorbic acid content in the leaves of NERICA mutant lines and their parents under rainfed condition. The experiment was conducted in the Biotechnology division of Bangladesh Institute of Nuclear Agriculture and in the laboratory of the department of Biochemistry and Molecular Biology, Bangladesh Agricultural University, Mymensingh. Proline and ascorbic acid contents were determinated by the method developed by Bates et al. 1973 and titrimetric method (Reo, 1954) respectively with three replication. As the experiment was conducted under rainfed condition and due to self-drought tolerance of NERICA lines, proline and ascorbic acid accumulate in significant amount. Free proline content in the leaves of mutant rice lines varied from 9.38 mg/100g to 25.46 mg/100g with a mean value of 17.59 mg/100g. Here maximum proline content was found in N1/300/P-8-3-3 (25.46mg/100g) and minimum in N4/350/P-2(1)-32-11 (9.38mg/100g). Ascorbic acid content in the leaves of rice plant varied from 1.12mg/100g to 1.98 mg/100g with a mean value of 1.59 mg/100g. Here maximum accumulation of ascorbic acid was found in N1/250/P-7-2-1 (1.98mg/100g) and minimum in N1/250/P-7-3-11 (1.12mg/100g). Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 419-424